The Indonesia's Financial Landscape: P2P Loan Growth, Bank Performance and The Covid-19 Connection - Kohardinata, Cliff; Suhardianto, Novrys; Tjahjadi, Bambang; Widianingsih, Luky Patricia (AKRUAL: JURNAL AKUNTANSI, 2024)
Introduction/ Main Objectives: This study investigated the impact of peer-to-peer (P2P) loan growth on banking credit growth in Indonesia, specifically focusing on regions with low and high-risk non-performing loan (NPL) banking, both before and during the exogenous shock of the COVID-19 pandemic. Background Problems: The digitalization of the banking industry faces a new challenge caused by start-up companies taking advantage of financial technology (FinTech) to create a new business model and financial innovation that can create financial solutions for the community. Research Methods: The research employed a panel regression model using monthly data from 33 provinces in Indonesia. The data spans from July 2019 to March 2020, representing the period before the COVID-19 pandemic, and from July 2020 to March 2021, covering the pandemic period. Finding / Results: The regression analysis of data from the pre-COVID-19 periods revealed that the P2P loan growth negatively affects the banking credit growth in the provinces with low-risk banking NPLs; while on the contrary, during the COVID-19 pandemic, the P2P loan growth positively affects the banking credit growth in the provinces with high-risk banking NPL. Conclusion: The complementary impact of the P2P platform on banking occurred during the COVID-19 pandemic, but banks must remain vigilant because the P2P platform had become a substitute for banking prior to the COVID-19 pandemic. Therefore, when the COVID-19 pandemic passes and the stimulus from the financial services authority is no longer valid, there are still potentials for the P2P platform to substitute banks in Indonesia.